Multiple mechanisms for transcriptional regulation of the myc gene family in small-cell lung cancer. - Krystal, G (1988)
The molecular mechanisms reported to regulate the expression of myc family genes are multiple and complex and include gene amplification, transcriptional activation, transcriptional attenuation, and mRNA stability. We have investigated which of these mechanisms are responsible for the extreme variation in myc gene family mRNA levels observed in human small-cell lung cancer cell lines. In addition to gene amplification, a block to nascent mRNA chain elongation, causing attenuation of transcription, is an important regulatory mechanism controlling the steady-state levels of c-myc and L-myc mRNA. The loss of transcriptional attenuation is correlated with overexpression of these two genes in cell lines which do not show gene amplification. Expression of c-myc mRNA appears to be dependent on promoter activity and attenuator function. In contrast, regulation of expression of the N-myc gene does not involve transcriptional attenuation; steady-state mRNA levels are correlated with promoter activity as well as gene amplification. We conclude that transcriptional regulation of each member of the myc gene family is accomplished by a different assortment of complex mechanisms, including gene copy number, promoter activation, and transcriptional attenuation. Interference at multiple points in this complex regulatory process appears to be an important mechanism by which small-cell lung cancer and other human tumors evade growth control.